My reference book (Chicago, ill., 2012)
For Grades 1-2, this resource contains explanations of key mathematical content, with directions to the Everyday Mathematics® games. A young learner's first mathematical reference book.
Keywords: Toán học,Mathematics; Dạy và học (Tiểu học),Study and teaching (Elementary)